A HYBRID REVIEW ON ISLAMIC CHARACTER EDUCATION IN INDONESIA - Rumbang Sirojudin; Wasehudin Wasehudin; Iwan Ridwan (Edukasi Islami : Jurnal Pendidikan Islam, 2026)
Islamic Character Education has become an increasingly important issue in contemporary education due to concerns regarding moral degradation, digital transformation, and the integration of religious values into modern learning systems. However, research examining the development and intellectual structure of Islamic Character Education remains limited. Therefore, this study aims to explore the evolution, theoretical foundations, contextual settings, characteristics, and methodological trends of Islamic Character Education research in Indonesia. This study employed a hybrid bibliometric and systematic literature review approach using the TCCM (Theory–Context–Characteristics–Methodology) framework. Data were collected from the Scopus database in April 2026 using keywords related to Islamic character, morality, ethics, values, and education without publication year limitation. The review process followed the PRISMA protocol, resulting in 50 selected articles for further analysis. The findings reveal that Islamic Character Education research has grown significantly, particularly after 2017, with dominant themes including moral education, akhlaq, Islamic values, pesantren education, curriculum integration, and digital transformation. The literature is mainly grounded in moral development theory, character education theory, social constructivism, and Islamic pedagogical ethics, while the research context is largely concentrated in pesantren, madrasah, and Islamic schools in Indonesia. Methodologically, qualitative approaches remain dominant, although quantitative, mixed-method, and digital-based studies have recently emerged. Overall, this study demonstrates that Islamic Character Education has developed into a dynamic and interdisciplinary research field, while future studies should focus on developing more contextually grounded Islamic educational theories and examining emerging issues related to artificial intelligence and global educational challenges.